The electronic health record in the general health system of Cyprus: A cross-sectional study - Periklis, Rompolas; Masouras, Panicos; Avgousti, Sotiris (My University, 2023)
Since 2019, Cyprus has introduced the EHR into its General Health System. During the period October – December 2022, a first cross-sectional study of users' opinions and attitudes was carried out using an electronic self-report questionnaire. The study involved 429 physicians. During the statistical processing of the data, the minimum value of the level of statistical significance was set at 5%. To measure scale reliability the Cronbach's Alpha coefficient was studied and Confirmatory Factor Analysis was used to check the validity of the scales. The good fit test of the model was done with the SRMR. The investigation of the relationship between the scales related to the use of EHR and demographic and occupational factors was carried out in two stages. Initially, bivariate analysis was performed using the Spearman index, the Point Biserial correlation index, while dispersion analysis (ANOVA) was also used. Multivariate analysis was then performed using Multiple Linear Regression. The results recorded a moderate degree of adoption of EHR functions, moderate efficiency, moderate degree of satisfaction and moderate overall evaluation of the EHR by users. Those with adequate training, technical support and familiarity with the use of EHR and ICT in general recorded higher scores, while users of older age and many years of professional experience recorded lower scores. The limitations of the study were the lack of a sample of other health professionals such as nurses, the timing of the implementation of the EHR with the covid-19 pandemic and the correlation of the results only with those of the international literature, due to the absence of Cypriot scientific data. In order to fulfill Cyprus' strategic goals on eHealth, health policy makers should proceed with improvement interventions aimed at integrating the EHR as an interoperable system. Education and support of users and equal access for all other health professionals are essential. Finally, new research must follow.
Keywords: Electronic health record; Users' opinions